2013
DOI: 10.1371/journal.pone.0067577
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms of the CASP8 Gene Promoter May Not Be Associated with Colorectal Cancer in Han Chinese from Southwest China

Abstract: PurposeCaspase 8 (CASP8) plays a critical role in the apoptotic pathway and aberrant regulation of this pathway causes many diseases including cancers. Genetic variants rs3834129 (CTTACT/−) and rs3769821 (T/C) in the promoter region of the CASP8 gene were documented to be associated with multiple solid cancers and non-Hodgkin’s lymphoma (NHL), respectively, despite of some controversies. We aimed to discern potential association of these two variants and rs113686495 (CTGTCATT/−), as well as CASP8 mRNA and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…This study recruited 6,733 CRC cases and 7,576 controls by six different centers located in Spain, Italy, USA, England, Czech Republic and the Netherlands collaborating to the international consortium COGENT (Colorectal cancer GENeTics). Such null associations were also presented in a study conducted by Xiao MS et al in Chinese population using 305 CRC patients and 342 healthy individuals 20 .…”
Section: Discussionsupporting
confidence: 60%
“…This study recruited 6,733 CRC cases and 7,576 controls by six different centers located in Spain, Italy, USA, England, Czech Republic and the Netherlands collaborating to the international consortium COGENT (Colorectal cancer GENeTics). Such null associations were also presented in a study conducted by Xiao MS et al in Chinese population using 305 CRC patients and 342 healthy individuals 20 .…”
Section: Discussionsupporting
confidence: 60%
“…Manual search of references cited in the published studies did not reveal any additional articles. As a result, a total of six relevant studies containing 6,325 cases and 6,842 controls were included in the meta-analysis [8] , [19] , [20] , [21] , [22] , [23] ( Figure S1 ). Table 2 lists the main characteristics of these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Among these publications, two were conducted in Caucasian descent [20] , [21] , and four were conducted in Asian descent [8] , [19] , [22] , [23] . Three were population–based studies [8] , [21] , [22] and three were hospital–based studies [19] , [20] , [23] . Two of these studies [19] , [22] presented CASP8 −652 6N ins/del polymorphism genotype distributions according to cancer location (colon cancer and rectal cancer).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of Caspase 8 (CASP8), represents an important initiating event in the death receptor-induced apoptosis gene. However, the deleted allele of the CASP8 polymorphism has been associated with decreased risk for cervical cancer in a Chinese population (136). Studies in African populations have not found any association between CASP8 polymorphisms and cervical cancer susceptibility (65).…”
Section: Iii) Molecular Genetic Variations Genes Chromosomes Snps mentioning
confidence: 96%